2010
DOI: 10.1007/s10596-010-9179-1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive meshing in a mixed regime hydrologic simulation model

Abstract: Problems in hydrology frequently have moving fronts and dynamic driving mechanisms such as wells. Since the location of important features changes during a simulation, accurate modeling requires uniformly fine resolution or the ability to change resolution during the simulation. We will describe an algorithm for refinement and unrefinement of tetrahedral/triangular meshes that has been implemented in the adaptive hydrology (ADH) code. The codes including the refinement/unrefinement algorithms are implemented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The latter problem can be dealt with by either crushing it with massive parallel computing (Kollet, 2010), or by reducing it by avoiding redundant computations. This can be done by exploiting patterns of similarity in time via adaptive time stepping (Minkoff and Kridler, 2006), in space by adaptive gridding (Pettway et al, 2010;Berger and Oliger, 1984), or both (Miller et al, 2006). Due to their generality, adaptive methods have been used to improve distributed modelling of a large variety of systems such as the universe (Teyssier, 2002), the atmosphere (Bacon et al, 2000;Aydogdu et al, 2019), oceans (Pain et al, 2005), and groundwater systems (Miller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The latter problem can be dealt with by either crushing it with massive parallel computing (Kollet, 2010), or by reducing it by avoiding redundant computations. This can be done by exploiting patterns of similarity in time via adaptive time stepping (Minkoff and Kridler, 2006), in space by adaptive gridding (Pettway et al, 2010;Berger and Oliger, 1984), or both (Miller et al, 2006). Due to their generality, adaptive methods have been used to improve distributed modelling of a large variety of systems such as the universe (Teyssier, 2002), the atmosphere (Bacon et al, 2000;Aydogdu et al, 2019), oceans (Pain et al, 2005), and groundwater systems (Miller et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, groups of model elements are dynamically established and adjusted during model runtime by identifying and exploiting patterns of similarity in either time or space. Adaptive time stepping (Minkoff and Kridler, 2006) exploits patterns of similarity in time, and adaptive gridding (Pettway et al, 2010;Berger and Oliger, 1984) exploits patterns of similarity in space; combinations of both approaches are possible (Miller et al, 2006). Due to their generality, adaptive methods have been used to improve distributed modelling of a large variety of systems such as the universe (Teyssier, 2002), the atmosphere (Bacon et al, 2000;Aydogdu et al, 2019), oceans (Pain et al, 2005, and groundwater systems (Miller et al, 2006).…”
mentioning
confidence: 99%
“…Indeed even one-dimensional approximations have shown that they can pose a significant computational burden and benefit from adaptive resolution, depending on the combination of soil properties, initial conditions, and boundary forcing . However, despite the introduction of sophisticated adaption techniques that have have matured in other computational mechanics fields (Schwab, 1998;Rannacher, 2001;Fidkowski and Darmofal, 2011), including so-called h adaption which modifies the local mesh spacing (Pettway et al, 2010) as well as methods that vary the local mesh spacing and approximation order (i.e., h-p adaption) (Solin and Kuraz, 2011), spatial adaption for Richards' equation is still not widely used in practice.…”
Section: Spatial Discretizationmentioning
confidence: 99%